Interkulturowa kompetencja komunikacyjna w nauczaniu akcentuacji języka rosyjskiego - Woch, Joanna (Neofilolog, 2023)
Intercultural communicative competence in Russian word stress acquisition refers to effective and appropriate management of interaction in various conversational situations that require specific orthoepic habits in the area of contemporary Russian accentual system. Every natural communicative situation needs informal, spoken language rather that standard Russian taught in classroom environment. Therefore, contemporary spoken Russian with its accentual characteristics needs to be examined. The research conducted on the group of Russian, Belorussian and Ukrainian youtubers indicates that the analyzed speech contains some specific derivatives which are characteristic of colloquial Russian: semelfactive verbs and their past participle forms with stressed suffix -ну́(ть)/-ану́(ть), masculine derivatives with stressed suffix -о́с, neuter nouns with the suffix -ов(о)/-ев(о), masculine nouns with the stressed suffix -а́к/-я́к, -а́н/-я́н, -о́н, feminine nouns with an accented suffix -у́х(а)/-ю́х(а), deverbal nouns with suffix -ёж, diminutives with suffixes -чик, -у́шк(а)/-ю́шк(а), -а́шк(а)/-я́шк(а), relational adjectives with stressed suffix -о́в(ый). Furthermore, there is no significant difference between Ukrainian, Belorussian and Russian analyzed material in terms of accentuation apart from one tendency, which does not seem to appear in Russians’ speech. Ukrainians and Belorussians tend to stress root in short verbs of past tense feminine forms.